Augmenting the landscape scene: students as participatory evaluators of mobile geospatial technologies. Issue 2 (3rd April 2019) - Priestnall, Gary; FitzGerald, Elizabeth; Meek, Sam; Sharples, Mike; Polmear, Gemma
ABSTRACT: This paper provides a two-phase study to compare alternative techniques for augmenting landscape scenes on geography fieldtrips. The techniques were: a pre-prepared acetate overlay; a custom-designed mobile field guide; a locative media app on a smartphone; a virtual globe on a tablet PC; a head-mounted virtual reality display, and a geo-wand style mobile app. In one field exercise the first five techniques were compared through analysis of interviews and student video diaries, combined with direct observation. This identified a particular challenge of how to direct user attention correctly to relevant information in the field of view. To explore this issue in more detail, a second field exercise deployed "Zapp", a bespoke geo-wand-style app capable of retrieving information about distant landscape features. This was evaluated using first-person video and spatial logging of in-field interactions. This paper reflects upon the relative merits of these approaches and highlights particular challenges of using technology to mimic a human field guide in pointing out specific aspects of the landscape scene. We also explore the role of students acting as design informants and research co-participants, which can be mutually beneficial in promoting a critical appreciation of the role of technology to support learning about the landscape.